WITHDRAWING PRODUCTS FROM THE MARKET – A MAJOR COMPONENT OF COMPANY STRATEGY REGARDING CUSTOMER SERVICE - OANA DOBRE-BARON (Annals of the University of Petrosani: Economics)
Among the major components of company strategy regarding customer service there is the withdrawal of products from the market. This process is considered today by many companies to be a necessary evil in their relationship with consumers, who know their rights regarding products that may present risks. The present paper seeks to outline the main aspects related to this process and to emphasize the fact that economic operators on the Romanian market have recognized the importance of voluntary withdrawal campaigns of nonconforming or risk-prone products from the market as an element of conforming to national law, but more so as an instrument in the competitive fight for attracting and inducing loyalty in the customer-base.